한우 육성 비육 시 보리 급여수준이 증체와 육질에 미치는 효과 - 장선식; 홍성구; 이병석; 조영무; 조원모; 권응기; 백봉현; 송만강 (Journal of animal science and technology, 2006)
The present study was carried out to determine the effects of feeding levels of barley grain in diets of Hanwoo on the growth performance and carcass characteristics of Hanwoo. Twenty Hanwoo bull calves (initial mean body wt. 99kg) were randomly divided to examine the effects of 5 feeding levels of barley grains(addition levels: 0, 0 and 40% for FII40; 0, 0 and 60% for FII60; 0, 20 and 40% for F2040; and 0, 20 and 60% for F2060 during the growing, early fattening and late fattening periods, respectively) on growth performance and meat quality. Body weight was not affected by the feeding level of barley grains through the whole experimental period, although the body weight of Hanwoo bulls fed FII40 diet at 24 months old of age tended to be lower(591.5kg) than that of other animals(606.2～614.6kg). However, body weight gain in the bulls of the FII60 diet was slightly increased(P<.19). The feeding levels of barley grains did not influence on fasting body weight, carcass weight, carcass rate, lean meat, retailed cut, KPH fat and bone yield. The lean meat yield(89.82%) and fat yield(20.28%) tended to increase in Hanwoo bulls fed the F2060 compared with other treatments. Feeding of the diets of FII40 resulted in the higher marbling scores as 3.75, respectively than other diets. 본 연구는 보리의 급여수준이 한우수소의 성장과 육질에 미치는 효과를 조사하고자 실시되었다. 수송아지 20두(평균체중 99㎏)를 공시하여 한우수소의 육성비육 시 보리의 급여수준(육성기－비육전기－비육후기 보리 배합비; 0-0-40, FⅡ40; 0-0-60, FⅡ60; 0-20-40, F2040; 0-20-60, F2040)이 증체와 육질에 미치는 효과를 구명하였다. 시험기간 동안의 체중은 성장단계별 보리 급여수준 간 차이는 보이지 않았으나, FⅡ40구의 24개월령 체중이 591.5kg으로 606.2～614.6kg 내외의 다른 처리구에 비해 다소 감소된 경향이었다. 그러나 FⅡ60구는 비육후기에 보리 60% 첨가된 사료를 섭취하면서 증체가 개선되는 경향이 있었다(P<.19). 한우수소에 대한 보리위주 사료의 급여는 생체중, 도체중과 도체율, 정육률, 거래정육률 그리고 KPH 지방과 뼈의 비율 등의 도체특성에 있어 처리 간 차이는 없었으나, 보리를 비육전기에 20%, 비육후기에 60% 급여한 F2060구의 한우수소에서 정육률과 지방률이 각각 89.82, 20.28%로 다른 처리구에 비해 다소 높았으며, 이로 인해 거래정육률은 최대 5.5% 가량 낮게 나타났다. 근내지방도는 FⅡ40구 및 F2060구에서 각각 3.75, 3.60으로 다른 처리구에 비해 높은 편이었으며, 조직감 역시 FⅡ60구와 F2060구가 공히 1.6으로 다른 두 처리구에 비해 양호하였다.